2018
DOI: 10.1108/bfj-12-2017-0731
|View full text |Cite
|
Sign up to set email alerts
|

Alternative food networks: sustainable business models for anti-consumption food cultures

Abstract: Purpose The purpose of this paper is to analyse a sustainable business model (SBM) implemented by an Alternative Food Network (AFN), namely the Italian Food Assembly, with the goal of exploring its drivers of success and explaining how it can contribute to enhance sustainable and anti-consumption behaviours. This research aims at combining principles from both SBM innovation and user-driven anti-consumption and well-being habits, in order to develop more successful, comprehensive and community-centred sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…This study provides a comprehensive review on the applications of SBMs in different industries, [24], and Hirscher et al [38] have presented innovative approaches in which customers are engaged in the designing process to devise a sustainable value proposition. Hirscher et al [38], for instance, utilize do-it-yourself (DIY) and do-it-together (DIT) design strategies to design a more sustainable innovative value proposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides a comprehensive review on the applications of SBMs in different industries, [24], and Hirscher et al [38] have presented innovative approaches in which customers are engaged in the designing process to devise a sustainable value proposition. Hirscher et al [38], for instance, utilize do-it-yourself (DIY) and do-it-together (DIT) design strategies to design a more sustainable innovative value proposition.…”
Section: Discussionmentioning
confidence: 99%
“…They by combining principles from both SBM innovation and user-driven anti-consumption and well-being habits they intended to design a sustainable business model that enhance sustainable and anti-consumption behaviours.They studied the Italian Food Assembly, which is a successful example in Alternative Food Network (AFN). De Bernardi and Tirabeni[24] found out two main factors have caused Italian Food Assembly implemented a sustainable business model: 1) there is a strong knowledge sharing of sustainable consumption behaviours among the members and 2) there is an effective distribution of best practices among them also.…”
mentioning
confidence: 99%
“…De Bernardi and Tirabeni [36] perceive that designing a sustainable business model involves designing a community-centered sustainable value proposition. By combining principles from both sustainable business model innovation and user-driven anti-consumption and well-being habits they intended to design a sustainable business model that enhance sustainable and anti-consumption behaviors.…”
Section: Management and Marketingmentioning
confidence: 99%
“…They studied the Italian Food Assembly, which is a successful example in the Alternative Food Network (AFN). De Bernardi and Tirabeni [36] found that two main factors have caused Italian Food Assembly industry to implement a sustainable business model: 1) there is a strong knowledge sharing of sustainable consumption behavior among the members and 2) there is an effective distribution of best practices among them also.…”
Section: Management and Marketingmentioning
confidence: 99%
“…Many authors consider designing a sustainable value proposition as an approach to design a sustainable business model. In this regard, Geissdoerfer et al[24] , Biloslavo et al[25] , Oskam et al[26] , Tolkamp et al[32] , Baldassarre et al[33] , De Bernardi and Tirabeni[34] , and Hirscher et al[48] have presented innovative approaches in which customers are engaged in the design process to devise a sustainable value proposition. Hirscher et al[48] , for instance, utilize do-it-yourself (DIY) and do-it-together (DIT) design strategies to design a more sustainable innovative value proposition.…”
mentioning
confidence: 99%